2021
DOI: 10.1002/lno.11774
|View full text |Cite
|
Sign up to set email alerts
|

Fecal pellet production by mesozooplankton in the subarctic Northeast Pacific Ocean

Abstract: Mesozooplankton fecal pellets sinking from the sea-surface constitute an important component of the biological carbon pump, which is variable in part due to differences in zooplankton community composition on various scales. Particulate organic carbon production as fecal pellets by the entire mesozooplankton community has, until now, not been directly measured. We measured fecal pellet carbon (FPC) production rates of the mesozooplankton community separated into five size classes (0.2 to > 5.0 mm), and rates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 48 publications
1
21
1
Order By: Relevance
“…9, S7). These values are a bit lower, but still fairly consistent with the sampled cruise mean, though the high observed variability in Stamieszkin et al (2021) highlights the challenge in model-observation comparisons with snapshot studies at a single time point. Model comparisons with GZ-COBALT and sediment trap data, which integrates observations over longer time scales, will need to incorporate tunicate-specific POC sinking speeds and is a target for future work.…”
Section: Discussionmentioning
confidence: 68%
“…9, S7). These values are a bit lower, but still fairly consistent with the sampled cruise mean, though the high observed variability in Stamieszkin et al (2021) highlights the challenge in model-observation comparisons with snapshot studies at a single time point. Model comparisons with GZ-COBALT and sediment trap data, which integrates observations over longer time scales, will need to incorporate tunicate-specific POC sinking speeds and is a target for future work.…”
Section: Discussionmentioning
confidence: 68%
“…Salp fecal pellets have long been recognized to have an outsized and episodic influence on carbon export (e.g., Caron et al, 1989;Iseki, 1981), and their importance was reconfirmed during our month-long observations in the subarctic Pacific. The low numerical abundance of salp pellets increased the uncertainty of our estimates, but our observations still suggested that they attenuated little with depth, likely due to their rapid sinking speeds (>1,000 m d −1 , Phillips et al, 2009), but also perhaps due to diel vertical migration (Madin et al, 2006;Stamieszkin et al, 2021). The true effect of salp fecal pellets on carbon export is probably overlooked by many sampling programs, especially in the upper ocean where trap deployment durations are short and trap collection areas are relatively small.…”
Section: Discussionmentioning
confidence: 73%
“…9, S7). These values are a bit lower, but still fairly consistent with the sampled cruise mean, though the high observed variability in Stamieszkin et al (2021) highlights the challenge in model-observation comparisons with snapshot studies at a single time point. Model comparisons with GZ-COBALT and sediment trap data, which integrates observations over longer time scales, will need to incorporate tunicatespecific POC sinking speeds and is a target for future work.…”
Section: Marine Food Web and Biogeochemical Impactsmentioning
confidence: 68%
“…Given the boom-and-bust population dynamic of pelagic tunicates, they can often be found to dominate POC export when present (Madin et al, 2006;Smith Jr et al, 2014). Indeed, a recent study from a NASA EXPORTS cruise found that salp fecal pellets comprised up to 80% of the detrital production in the upper 100 m in the NE Pacific when present, though they contributed an average of 28% of fecal pellet carbon production over a month-long sampling period (Stamieszkin et al, 2021). In our 20-year model climatology, large tunicate detritus production comprises 20% of the total detritus production in the top 100 m from summer to early fall in the same region (Fig.…”
Section: Marine Food Web and Biogeochemical Impactsmentioning
confidence: 99%